(3GdOQQ GdcGefI dCYdGe GdeGFI GdKGefIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3JQLeI eMeO Hf CMeO Hf eMeO GdYPQi GdeGdbi s
(3BNQgG (B:s
(3JQLeI jhfS Hf eMeO Hf CjhH GdHYdi s
(3hgPg GdfSNI eShOI ajgG cKjQ ef GdEVGaGJ hGdGSJOQGcGJ Ydi MhGTjgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs